The Impact of Selected Essential Oils Applied to Non-Woven Viscose on Bacteria That Cause Lower Urinary Tract Infections—Preliminary Studies - Emilia Frydrysiak (MDPI AG, 2021)
Inflammation of the lower urinary tract is a very common problem, which occurs particularly in women. A concept of a biotextronics system for preventive and support treatment of lower urinary tract inflammations was presented. The system includes a non-woven viscose insert for essential oils application. The oils were deposited on the non-woven viscose and incubated in the temperature of 37 °C and served a model for their action in the vapor phase as the element of the biotextronics system. The essential oils used in the research were the following: chamomile (Matricaria chamomilla L.), sage (Salvia officinalis L. and Salvia lavandulaefolia), juniper (Juniperus communis L.), thyme (Thymus vulgaris L.), and mixtures of chamomile oil with oils of each sage species in a 1:1 ratio. The oils were tested against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus epidermidis, Staphylococcus saprophyticus, and Enterococcus faecalis. The best inhibitory effect in vapor phase was noted for chamomile essential oil at the lowest concentration (0.054 µL/cm3). Both mixtures of chamomile and sage acted antagonistically, lowering the antibacterial activity of the individual oils applied solely. Juniper and Salvia officinalis essential oils at the concentrations tested increased the growth of at least one of the bacteria tested. Salvia lavandulaefolia Vahl. essential oil inhibited all bacteria, only at the concentration 0.214 µL/cm3. The thyme oil, at the concentration 0.054 µL/cm3, reduced the growth of all bacterial species tested. Chamomile and thyme essential oils were chosen for further research in the biotextronics pantiliner system.